Kajian Psikoanalisis Karakter Rara Pada Film Imperfect - CahyaPutra, Dhandy Perkasa CahyaPutra; Kartika, Bambang Aris; Suharijadi, Didik (Universitas Jember, 2025)
Imperfect is a film directed by Ernest Prakasa and based on his wife Meira's book called Imperfect: A Journey to Self-Acceptance airing on December 19, 2019. Imperfect tells the story of a woman named Rara (Jessica Milla), an employee at a cosmetics company who doubts her body shape because she doesn't meet the beauty standards of others. The method used in this research is a qualitative research method using Sigmund Freud's psychoanalytic theory as the main theory and Bordwell's mise en scene theory as a supporting theory in analyzing Rara's character in the film Imperfect. The division of scenes is based on the mise en scene aspect and considers the physical changes in Rara's character as a comparison for changes in attitude and character. This research identifies two forms different of Rara's character present in the 8 scene. Provides a deeper understanding of how visual elements in film, such as setting, costume and makeup, lighting, and staging, collaborate to construct a powerful concept of psychoanalytic character within a scene. The conclusion of this research reveals that mise-en-scene plays a pivotal role in shaping the perceived emotional Rara's character into audience. The demands of beauty standards dominate most segments in this scene. Rara's determination to make physical changes is supported by the mise-en-scene aspect. The results of the physical changes made Rara's career dreams come true. Physical changes and appearance also dominate Rara's character, becoming selfish and arrogant, thereby losing the people around her.